(untitled) (TAJ: Journal of Teachers Association, 2020)
Congenital hypothyroidism is the commonest preventable cause of mental retardation. It is more prevalent in endemic goiter regions like Bangladesh. This study was done to assess the congenital hypothyroidism in neonates (age 4 to 28 days) admitted in Rajshahi Medical College Hospital. It was a cross sectional descriptive study conducted at pediatric department of Rajshahi Medical College Hospital from July 2016 to June 2018. After taking written consent from each mother/guardian, 3 ml venous blood was collected and sent to the laboratory of Institute of Nuclear Medicine and Allied Sciences, Rajshahi to estimate serum TSH/ serum TSH and T4 level. Total 500 samples were collected in two years of study period. All information was put in the data collection sheet and was analyzed through standard statistical method by using SPSS version 16.0. Serum level of TSH ≥ 20 μIU/ml was considered as congenital hypothyroidism. Serum level increased but bellow 20μIU/ml were recalled to repeat serum TSH level within 2 to 6 weeks of age. Among 500,321(64.2%) male and 179 (35.8%) female, Among 500 study population, 199 and 135 came from Rajshahi and Chapai Nawabganj district respectively. Total 7 mothers were hypothyroid and on thyroid replacement therapy. TSH level above 20 μIU/ml was found in 5 neonates, 11 to 20 μIU/ml in 7 neonates. After repeat TSH testing one infant had serum TSH level above 20 μIU/ml. Finally total 6 infants were diagnosed as having congenital hypothyroidism. Thus frequency of congenital hypothyroidism was 1.2%. Congenital hypothyroidism in Rajshahi region is very high in relation to global incidence. Although this is not the actual picture of our country but this figure is alarming. Therefore neonatal screening program should be started as soon as possible to reduce the number of mentally retarded child. Maternal obesity and thyroidal status have significant association with neonatal TSH level. TAJ 2019; 32(2): 36-42